Extraction and purification of Ferritin from liver tissue - R Behjati Ardakani (Babol University of Medical Sciences, 2005)
Background and Objective: Ferritin with molecular weight of 450 kDa is the most important iron storage protein and is made of 24 subunits consisting of light and heavy chains. Each Ferritin molecule is able to store 4500 Fe3+ molecules. The aim of this study was to determine the preparation of highly pure Ferritin for usage in diagnostic and research systems. Methods: In this study, Ferritin was extracted and purified by homogenizing liver tissue, heating at 75 degrees centigrade, ammonium sulfate fractionation and gel filtration chromatography on sephadex G-200 column. The purity of Ferritin was improved by using recycling chromatography. Resulted protein was electrophoresed on polyacrylamide gel in the presence of sodium dodecylsulfate (SDS-PAGE). Existence of Ferritin was confirmed by ELISA test and potassium ferricyanide staining of gel. Silver nitrate staining of gel was used to confirm the purity of Ferritin. Electrophoresis of Ferritin under reducing conditions in presence of 2-mercapto ethanol was done to show the subunits (19 and 21 kDa) of ferritin. Findings: This purification method resulted in very pure Ferritin and the yield was 100 µg/gr of wet liver tissue. Electrophoresis of Ferritin under reducing conditions in presence of 2-mercapto ethanol showed the both subunits (19 and 21 kDa) of Ferritin. Conclusion: Highly pure Ferritin resulted by this method in appropriate for diagnostic and research purpose and the yield is reasonable comparing other studies.